Improvement of Learning Outcomes in Theme 3 Of Healthy Food Through Audio-Visual Assisted Discovery Learning in Elemenatry Schools - Marwanto Marwanto (Universitas Sebelas Maret, 2020)
This article describes the improvement of student learning outcomes in the thematic learning of healthy food for the content of science subjects with the discovery learning method through audio-visual. This research is a classroom action research (CAR) which was conducted in 2 cycles, each cycle consisting of planning, implementation, and reflection stages. The subjects of this study were 28 students of class V SDNGandrungmangu 01 Cilacap in the academic year 2020/2021. Data collection techniques using tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Discovery learning can improve student learning outcomes in thematic learning Healthy food for science subject content for class V SDN Gandrungmangu 01 academic year 2020/2021 as evidenced by a percentage of 65% completeness of learning outcomes in the cycle I, 75% in cycle II.